Molecular characterization of the heterogeneity of satellite cell populations isolated from an individual Turkey pectoralis major muscle - Yu, Hui; Li, Zhenyang; Yimiletey, Joseph; Wan, Chunmei; Velleman, Sandra (Frontiers in Physiology, 2025)
Satellite cells (SCs) are myogenic stem cells responsible for post hatch muscle growth and the regeneration of muscle fibers. Satellite cells are not a homogenous population of cells within a muscle and have variable rates of proliferation and differentiation even within a single fiber type muscle like the turkey pectoralis major muscle. In this study, the single satellite cell clones derived from the same turkey pectoralis major muscle with different proliferation rates were compared. The clones were classified as either fast-growing (early clone) or slow-growing (late clone) SCs. To thoroughly examine the molecular differences between these two groups, RNA sequencing was conducted to compare their transcriptomes following 72 h of proliferation. Principal Component Analysis confirmed that the transcriptomic profiles of early- and late-clones are markedly distinct. Differential gene expression analysis identified over 5,300 genes that were significantly differentially expressed between the two groups of cells. Gene ontology analysis showed that genes highly expressed in early clones are responsible for the fundamental aspects of muscle biology, including muscle tissue development and structural maturation. Conversely, genes upregulated in late clones are involved in cell-cell communication, extracellular matrix interactions, signal ligand activity, and cytokine activity—key components for forming an extracellular niche essential for functional satellite cells maintenance. Further examination of specific gene ontology categories such as muscle structure development and extracellular matrix components indicated significant differences in gene expression patterns between early- and late-clones. These findings highlight the genetic and functional diversity of SCs in turkeys. The distinct roles of these satellite cell populations indicate that a balance between them is necessary for preserving the normal physiological functions of SCs.